Benchmarking an 11-qubit quantum computer - Wright, K. (Nat Commun, 2019)
The field of quantum computing has grown from concept to demonstration devices over the past 20 years. Universal quantum computing offers efficiency in approaching problems of scientific and commercial interest, such as factoring large numbers, searching databases, simulating intractable models from quantum physics, and optimizing complex cost functions. Here, we present an 11-qubit fully-connected, programmable quantum computer in a trapped ion system composed of 13 (171)Yb(+) ions. We demonstrate average single-qubit gate fidelities of 99.5[Formula: see text] , average two-qubit-gate fidelities of 97.5[Formula: see text] , and SPAM errors of 0.7[Formula: see text] . To illustrate the capabilities of this universal platform and provide a basis for comparison with similarly-sized devices, we compile the Bernstein-Vazirani and Hidden Shift algorithms into our native gates and execute them on the hardware with average success rates of 78[Formula: see text] and 35[Formula: see text] , respectively. These algorithms serve as excellent benchmarks for any type of quantum hardware, and show that our system outperforms all other currently available hardware.